Identification of Lauric Acid as a Potent Sodium Channel NaV1.5 Blocker from Compound Chinese Medicine Wenxin Keli - Xie W; Gao J; Liang Y; Huang C; Zhang B; Chen X; Yao X; Nan G; Wu H; Wang Y; Wu L; Wang T; et al. (Drug Design, Development and Therapy)
Weiwei Xie,1,* Jiaming Gao,2,* Yingran Liang,1,* Chenxing Huang,3 Boyong Zhang,1 Xiaonan Chen,1 Xi Yao,1 Guo Nan,1 Honghua Wu,1 Yuefei Wang,1 Lin Wu,4 Taiyi Wang,3,5 Yan Zhu1 1State Key Laboratory of Component-Based Chinese Medicine, Tianjin University of Traditional Chinese Medicine, Tianjin, 301617, People’s Republic of China; 2Institute of Basic Medical Sciences of Xiyuan Hospital, Beijing Key Laboratory of Pharmacology of Chinese Materia, Beijing, 100091, People’s Republic of China; 3Institute of Acupuncture and Moxibustion, Shandong University of Traditional Chinese Medicine, Jinan, 250355, People’s Republic of China; 4Department of Cardiology, Peking University First Hospital, Beijing, 100034 People’s Republic of China; 5Shandong Key Laboratory of Innovation and Application Research in Basic Theory of Traditional Chinese Medicine, Shandong University of Traditional Chinese Medicine, Jinan, 250355, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yan Zhu, State Key Laboratory of Component-based Chinese Medicine, Tianjin University of Traditional Chinese Medicine, Beihua South Road, JingHai District, Tianjin, 301617, People’s Republic of China, Tel +86 22 59596168, Email yanzhu.harvard@icloud.com Taiyi Wang, Shandong Key Laboratory of Innovation and Application Research in Basic Theory of Traditional Chinese Medicine, Shandong University of Traditional Chinese Medicine, Jinan, 250355, People’s Republic of China, Email wangtaiyi@sdutcm.edu.cnPurpose: The major cardiac voltage-gated sodium channel NaV 1.5 (INa) is essential for cardiac action potential initiation and subsequent propagation. Compound Chinese medicine Wenxin Keli (WXKL) has been shown to suppress arrhythmias and heart failure. However, its active components have not been fully elucidated. This study focused on identifying the active inhibitor of INa in WXKL and exploring their mode of action in electrophysiological conduction.Methods: A chemical fraction library was constructed from an aqueous extract of WXKL and screened using an automated patch-clamping system in cells stably expressing the NaV 1.5 gene SCN5A. Candidate fractions with INa-inhibition activity were analyzed by HPLC-ESI-IT-TOF-MS and GC-MS to identify the ingredients. NaV 1.5 blocker molecules identified by single-cell electrocardiogram were tested in hiPSC-derived cardiomyocytes. We evaluated the SCN5A inhibitory potential of Wenxin Keli effective monomer employing molecular docking and molecular dynamics simulation approaches.Results: A primary screen of the WXKL chemical library identified five fractions that significantly inhibited the NaV 1.5 channel, with one of them rich in poly-saturated fatty acids. Molecular structural characterization revealed the presence of lauric acid, myristic acid, palmitic acid, and stearic acid in the active subfraction. Electrophysiological characterization demonstrated lauric acid (LA) as the most effective monomer for INa-inhibition with an IC50 at 27.40 ± 12.78 μM. LA shifted the steady-state inactivation of INa to more negative potentials and decreased the amplitude of extracellular field potential in hiPSC-derived cardiomyocytes. We demonstrate for the first time that naturally poly-saturated fatty acid, lauric acid, as a potential novel INa blocker. Molecular docking and molecular dynamics simulation suggested that LA binds to the NaV 1.5 protein, with a significant binding affinity forming interactions with functionally essential residues and blocks the inward flow of Na+. Mechanistically, lauric acid acts on the fast inactivation of NaV 1.5 alter electrophysiology conduction of hiPSC-derived cardiomyocytes and contribute to the antiarrhythmic effect of WXKL.Conclusion: Lauric acid is a potent blocker for sodium channel NaV 1.5 and alleviates arrhythmia via inhibiting INa. Keywords: lauric acid, Wenxin Keli, cardiac arrythmia, NaV 1.5 sodium channel, patch clamp recording, high-throughput electrophysiology